2018
DOI: 10.1111/jvh.12880
|View full text |Cite
|
Sign up to set email alerts
|

Viral activity and outcome of hepatitis B surface antigen‐positive grafts in deceased liver transplantation

Abstract: Indications of liver transplantation are extensive, but deceased donation does not meet the demand. Hepatitis B surface antigen (HBsAg)-positive grafts used to be discarded in the past. The aim of this study was to examine viral activity and outcome of HBsAg-positive deceased grafts transplanted to HBsAg-positive recipients. Eleven HBsAg-positive deceased grafts were transplanted to HBsAg-positive patients with acute liver failure (3 patients), hepatocellular carcinoma (6 patients) and repeatedly bleeding vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…No difference was shown in the incidence of liver dysfunction post‐LT, early and long‐term complications between the two groups, but the 1‐, 3‐ and 5‐year HBV recurrence (defined as quantitative HBV DNA > 100 copies/mL) was significantly higher in the former group (5.85% vs 1.97%, 11.63% vs 4.46% and 17.94% vs 4.46%, respectively, P = .016). In a small series of 11 patients transplanted with HBsAg‐positive grafts and treated with NAs, HBV DNA became undetectable in all patients until the end of the first year and remained undetectable during a mean of 40 months post‐LT 110 . Although the mechanisms of protective role of HBIG are not well understood, it has been hypothesized that HBIG may act not only by binding with circulating viral particles but also by decreasing hepatocytes HBsAg secretion and increasing cell‐mediating cytotoxicity or immune tolerance of infected hepatocytes 14 .…”
Section: Transplanting Grafts Of Hbsag‐positive Donorsmentioning
confidence: 99%
“…No difference was shown in the incidence of liver dysfunction post‐LT, early and long‐term complications between the two groups, but the 1‐, 3‐ and 5‐year HBV recurrence (defined as quantitative HBV DNA > 100 copies/mL) was significantly higher in the former group (5.85% vs 1.97%, 11.63% vs 4.46% and 17.94% vs 4.46%, respectively, P = .016). In a small series of 11 patients transplanted with HBsAg‐positive grafts and treated with NAs, HBV DNA became undetectable in all patients until the end of the first year and remained undetectable during a mean of 40 months post‐LT 110 . Although the mechanisms of protective role of HBIG are not well understood, it has been hypothesized that HBIG may act not only by binding with circulating viral particles but also by decreasing hepatocytes HBsAg secretion and increasing cell‐mediating cytotoxicity or immune tolerance of infected hepatocytes 14 .…”
Section: Transplanting Grafts Of Hbsag‐positive Donorsmentioning
confidence: 99%
“…De novo HBV infection was observed in 4.7% (3/64) of HBs Ag‐negative recipients who received HBc positive liver with lamivudine, but no de novo infection was observed with entecavir prophylaxis (0/44). Furthermore, Lee et al reported that HBsAg‐positive deceased liver grafts worked well in HBsAg‐positive recipients with minimal viral activity under the treatment of combined antiviral nucleoside and nucleotide analogs. The use of HBsAg‐positive deceased grafts may be feasible for HBsAg‐positive patients and can increase the donor pool to rescue dying patients.…”
Section: Liver Transplant Donormentioning
confidence: 99%
“…All the recipients of HBsAg positive allografts remained HBsAg positive without evidence of HBV hepatitis and were mainly receiving oral antiviral therapy without HBIG. Closer examination of viral activity suggests that there is low level viremia early on after LT with HBsAg positive donors but this becomes undetectable within a few months[61].…”
Section: Risks Associated With Post-liver Transplant Hcv Infectionmentioning
confidence: 99%